O Programa Bolsa Família (PBF) e as condicionalidades na educação: do surgimento aos tempos da Covid-19 - Santos, Celyane Souza dos (2022)
The Dissertation on screen, entitled “THE BOLSA FAMÍLIA PROGRAM (PBF) AND CONDITIONALITIES IN EDUCATION: from the emergence to the times of COVID-19”, seeks to understand and critically analyze the role played by the PBF, from the conditionalities in education, since its inception. creation, in 2003, until the acute phase of the COVID-19 Pandemic. As a consequence of the PBF expansion process, cash transfers to poor and extremely poor Brazilian families rose continuously over a period of more than a decade. Among the beneficiary families, the transfer received proved to be relevant, especially as a result of the criteria of counterparts, seen by a portion of civil society and the academic environment as a merit of the program, while there were negative criticisms of it. Despite the controversies, the trend was its increasing consolidation over time, to consider school attendance as an instrument of social insertion and citizenship mechanism. It is worth mentioning that Brazilian education, in the context of the pandemic, needed adjustments in its teaching model by targeting the remote system, which, in turn, was not enough to offer a teaching that promoted learning with egalitarian school coverage among the students. social segments. From this, the discussion around conditionalities in education has become increasingly urgent in the face of adversity. Thus, in order to achieve the proposed objectives, this Dissertation was based on the Historical-Dialectical Materialist Method, using bibliographic and documentary research, through data from the Knowledge Repository of the Institute of Applied Economic Research (RC-IPEA), from the Management of the Bolsa Família Program (SIGPBF), the Brazilian Institute of Geography and Statistics (IBGE), the National Household Sample Survey (PNAD-Continuous), the Ministry of Education, the Ministry of Health and the United Nations (UN) ). In addition, access to renowned authors who address the theme was integrated into the process, as well as the use of theses, dissertations, scientific articles, among others. As a result of the research, it is indicated that the monitoring of school attendance was incipient, due to the absence of strategies at the federal level; that is, the construction of effective and efficient tactics within the Union, states and municipalities. These consequences refer to non-monitoring due to absenteeism through the Ministry of Education.